KOMUNIKASI PEMERINTAHAN OTORITA IBU KOTA NUSANTARA DALAM MELAKSANAKAN PERSIAPAN PEMBANGUNAN DAN PEMINDAHAN IBU KOTA NUSANTARA (IKN) - Marihot Pandapotan Sinaga; Neneng Yani Yuningsih (Halu Oleo University, 2025)
This study analyses how the Nusantara Capital Authority (OIKN) conducts government communication during the preparation, development, and relocation stages. The research employs a qualitative case study method through in-depth interviews with OIKN officials, affected communities, and academics, complemented by document analysis and observation of OIKN’s communication media. Data were analysed using Miles and Huberman’s interactive model. The findings show that OIKN communicates through various channels (official website, social media, cultural forums, press releases) but still faces challenges. In openness, access to substantive information remains limited, and public participation in policymaking is minimal. In reliability, inconsistencies occur between the central government and OIKN, especially regarding funding and construction schedules. In intelligibility, the use of technical language hinders public understanding of spatial plans and development impacts. In interactivity, communication is largely one-way, with participatory forums often ceremonial and unresponsive to public concerns. The study suggests that OIKN’s communication should be strengthened through greater data transparency, message consistency, the use of plain language, and the establishment of deliberative public participation mechanisms. These efforts are crucial to reinforce the legitimacy of the capital relocation and foster public trust in the government.